FACTORS THAT MOST INFLUENCE THE ATTRACTION OF MOVEMENT TOWARDS SMKN-1 PALANGKA RAYA - Sinaga, Betty Setiawaty; Tarita Aprilani Sitinjak; Revianti Coenraad (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2025)
Transportation is a very important field of activity and has a strategic role for Indonesia. The city of Palangka Raya is the capital of the province of Central Kalimantan, Indonesia and has a population of 266,020 people (2020) with an average density of 93.24 people/km². The research location is at SMKN-1 Palangka Raya Jl. Tambun Bungai, Langkai, Jekan Raya, Palangka Raya City by distributing questionnaires to respondents who travel to SMKN-1 Palangka Raya by car, motorbike and pedestrian, so that they know the factors that most influence the attraction of movement to SMKN-1 Palangka Raya. The survey results show that there are differences in the movement of modes of instruction for students at SMKN-1 Palangka Raya. The largest mode of delivery was on Friday 282 SMP/hour and the smallest was on Monday 143 SMP/hour at SMKN-1 Palangka Raya. Several factors that most influence the strength of the movement towards SMKN -1 Palangka Raya are the number of students (X2) and the total number of teachers & employees (X4). Meanwhile, the land area (X1), the number of rooms (X3), the parking area (X5) are excluded. because it has a constant value or does not experience changes in value so the influence is less strong on the pull of movement. In future research, more than 1 number of schools can be carried out so that it can be significantly larger and can also be compared with existing research and add other variables to get a significant comparison.